POLA PEMBERDAYAAN MASYARAKAT DI HULU SUB DAERAH ALIRAN SUNGAI MIU (Kasus Penerapan Program SCBFWM di Desa Winatu Kecamatan Kulawi Kabupaten Sigi Provinsi Sulawesi Tengah) - Hafizi, Muh Zaynal; Golar, Golar; Sudhartono, Arief (Jurnal Warta Rimba, 2016)
Sub watershed catchment area of Miu river is located at Sigi Regency  that has 70.494,5 hectare width. Part of the watershed become critical land since the community has less understanding and knowledge in land management.   The community use the land just for economic reason that is for fullfill their daily need without think about how to manage the land in right way so that land still in productive condition along time. This research aims are: (a) Knowing pattern of empowering commnunity, (b) Identifiying community group that involved on empowering activities, (c) Knowing accompanying methode on applied empowering community program, (d) Knowing obstacles on applied empowering community activities at upstream of sub watershed catchment area of Miu river. This research used interviewing methode, and as respondence are field facilitators and community.  The research data collecting include primary and secondary datas. The primary data need to answer research aims, while the secondary data need as supporting data analysis. The research result shown that empowering community activity in Winatu village has succed in target reaching, and can give contribution on SCBFWM project persistence. Pattern of empowering community that is given by SCBFWM project are establishment of farming group (CBO) Ulu Miu Pewatua, independency training to the group, contonuous socialization, land rehabilitation, developing agicultural and animal husbandry efforts, and  improvement on structure of farming group institution. The obstacles on empowering commnunity process direct to the non technicalproblems i.e. access problems to the location, activity level of the community and the topography condition of hilly Winatu village.Keywords: empowering community, Miu river, pattern, SCBFWM, watershed catchment.